Kompetensi Perawat dan Tingkat Keterlaksanaan Kegiatan Perawatan Kesehatan Masyarakat - Suprapto Suprapto; Herman Herman; A Syamsinar Asmi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: health development is a way to increase awareness, willingness, and ability to live healthy for everyone in order to realize an optimal degree of public health. Method: This type of research is non-experimental with a quantitative approach, and correlation analytics. The population of all nurses who work at the puskesmas in Makassar is 118 people who meet the inclusion criteria in their selection. Results: there was no relationship between knowledge and the level of implementation of the social security activities. Conversely, there is a relationship between attitudes, skills, and competencies with the level of implementation of public health activities and that there is an interaction between competence and training so that the two variables affect each other. Conclusion: that there is a relationship between attitudes, skills and knowledge in the implementation of community health activities. Most dominant with the implementation of the social security program is the interaction between competence and training